If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + -9 = 12 + y Reorder the terms: -9 + n = 12 + y Solving -9 + n = 12 + y Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + n = 12 + 9 + y Combine like terms: -9 + 9 = 0 0 + n = 12 + 9 + y n = 12 + 9 + y Combine like terms: 12 + 9 = 21 n = 21 + y Simplifying n = 21 + y
| Y=x^2-3x-54 | | -3(2s-4)-12=-2(6s+4)-2 | | (5x+1)+(x+11)=180 | | 2r^2+17r+35=0 | | (5y*y)-1=0 | | (5x+3)+83=180 | | 0.45x+.015(16-X)=.10(-48) | | 12z^2-23z+10=0 | | 5x^2-10x-315=0 | | -3(4s-4)-12=-2(9s+1)-3 | | .15(10000)-.07y=.03(y+10000) | | 3p^2+8p+4=0 | | .60x+.05(18-x)=.10(97) | | x*x=20 | | .16(18)+.04x=.08(24+x) | | -2p+7=6-(4p+8) | | -6x=-4x-8 | | 7x^2-65x-50=0 | | 4(3x-9)=12(x-3) | | 6(4x-8)=3(8x+6) | | 7+2t-1=5t+7-2t | | 8x-24=4x | | -7x+6=83 | | y=13x-10 | | 4x+10=82 | | -28=12x-4 | | 6y+7=3+2(y-4) | | -2x+7=37 | | 9x-11=5x+11 | | 6x+34=14x-30 | | 3-a=4w-9 | | -9(5+r)=36 |